Identifikasi Tipologi Signage Wisata Sebagai Optimalisasi Cagar Budaya dalam Pengembangan Pariwisata di Banda Aceh - Alidha, Seprina Yana; Nisa Putri Rachmadani; Alfikhairina Jamil (Jurnal Serambi Engineering, 2026)
Tourism signage in cultural heritage areas plays a crucial role as a visual information element that enhances visitors’ experiences and reinforces the destination’s identity. Unsynchronized signage design and placement can reduce tourist comfort and weaken the overall attractiveness of the area. This study aims to examine the existing conditions and identify the visual and informational characteristics of tourism signage in the cultural heritage areas of Banda Aceh. The research employs a qualitative descriptive approach through direct observation, visual documentation, and a literature review on wayfinding design and visual communication principles. The findings indicate that the integration of design, cultural context, and informational functions is essential to create a meaningful visitor experience. Classification based on visual design characteristics reveals significant variations in typology, quality, and design integration across locations. Most signage is directive or regulatory in nature, with limited interpretive elements that convey historical narratives effectively. Wayfinding signage is relatively adequate in key points such as PLTD Apung but lacks holistic integration in more complex areas like Pintu Khop and Baiturrahman Grand Mosque. In terms of visual design, inconsistencies were found in readability, materials, and typography, which often fail to align with local cultural identity. Overall, Banda Aceh’s signage system remains suboptimal in supporting the educational and narrative functions of its heritage tourism.